Use of the GnRH Antagonist Elagolix for Endometriosis in Relation to Hypoestrogenic Effect in Women - Keisha Hillary Pangalila; Silvana Putri Tarigan; Viona Heryani Arla; Wahyu Irawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The female reproductive system is a system related to reproduction, which includes hormones and reproductive organs. Endometriosis is a disease that attacks the female reproductive organs. Endometriosis is the growth of endometrial cells that are not in place so that it interferes with the female reproductive system. Endometriosis causes pelvic pain and infertility in women. Endometriosis can be treated in several ways. One is to use drugs such as the GnRH antagonist Elagolix. This study aims to find out more about endometriosis and the Elagolix treatment in dealing with it. The method used in this study is a literature review method by discussing four focus studies to achieve the objectives of the study. Endometriosis is caused by several causes such as genetics, immunology, retrograde menstruation, coelomic metaplasia and vascular and lymphatic spread. The result of Endometriosis is the occurrence of dysmenorrhea, dyspareunia to infertility for the sufferers. The treatment that can be applied to endometriosis is surgical and medical surgery. One treatment with medical therapy is using Elagolix to inhibit the growth of endometriosis tissue by suppressing the hormone estrogen. Through this research, researchers are grateful that humans are given reason and thoughts by God so that humans can further research endometriosis and continue to try and try various alternative treatments to cure sufferers. The knowledge gained by humans is also very helpful for each other, namely the women sufferers so that they can live a better life to get rid of endometriosis. The conclusion obtained is that Elagolix is ​​one of the latest alternative treatments that can treat endometriosis.